The Effect of Corporate Social Responsibility on Profitability in Mining Companies Listed on The IDX in 2020-2023 - Imbang, Kezia; Karamoy, Herman; Mawikere, Lidia (Universitas Sam Ratulangi, 2024)
Corporate Social Responsibility is the company’s responsibility to stakeholders with respect to ethical, social and environmental issues. This study aims to determine the effect of corporate social responsibillity (CSR) on profitability as measured using return on assets (ROA). The object of this research is mining companies listed on the Indonesia Stock Exchange in 2020-2023. The analysis model used is simple linear analysis. This study uses secondary data in the form of annual reports and financial reports from mining companies lised on the Indonesia Stock Exchange in 2020-2023. From the results of this study it can be concluded that corporate social responsibility (CSR) has a significant negative effect on return on assets (ROA).